THE LEADERSHIP ROLE OF THE PRINCIPAL IN IMPROVING TEACHER PERFORMANCE IN ONLINE LEARNING AT SDN 08 KAMPUNG GADANG 2019/2020 - Rosmiwati Rosmiwati (JOURNAL INTERNATIONAL ON GLOBAL EDUCATION, 2022)
The objectives of this study are: (1) To describe how the role of the principal in improving teacher performance in the online learning process at SD Negeri 08 Kampung Gadang . (2) To describe how the performance of teachers at SD Negeri 08 Kampung Gadang . (3) To describe the inhibiting factors of the principal's leadership role in improving teacher performance. (4) To describe solutions in overcoming obstacles that occur. The type of research used is descriptive research with qualitative research methods with data collection techniques through interviews, observation and documentation. The data analysis technique uses data collection, data reduction, data display, and verification and confirmation of conclusions. The results of the study concluded: (1) The role of the principal in improving teacher performance in the online learning process has been carried out well, although there are several obstacles. (2) Teacher performance has implemented three indicators, namely personality and dedication, processes such as professional development, results such as teaching abilities. (3) Inhibits the lack of teacher expertise in using internet media for online learning, students who do not have Android, and lack of parental attention. 4. The solution is that teachers are required to attend training, coaching, outreach to parents and teacher visits to students' homes.